Towards learining organisations: mainstreaming experience capitalization in Latin America - Sancho, Federico (Technical Centre for Agricultural and Rural Cooperation, 2019)
The Inter-American Institute for Cooperation in Agriculture (IICA) was one of the implementing organisations of the experience capitalization project led by CTA, preparing the necessary tools and organising training courses throughout Latin America. This paper documents the steps taken by the Institute to adopt and to support the adoption of the experience capitalization approach during the past 18 months, working together with partners and organisations in different contries in the region